Pelatihan Komunikasi Persuasif Guna Meningkatkan Kompetensi Komunikasi Pengurus Lembaga Swadaya Masyarakat “Kakak Asuh” - Mauly Arzak Julika; Dwi Ulina Sari; Mahisa Dwi Prastowo (Lembaga Pengembangan Kinerja Dosen, 2025)
In addition to improving interpersonal communication skills, this training also emphasized the importance of strategic communication in the context of advocacy and social mobilization. NGO administrators were trained to design campaign messages tailored to audience segments, including potential donors, corporate partners, and government stakeholders. An understanding of the importance of framing and emotional appeal was also emphasized, so that the messages delivered were not only informative but also able to inspire empathy and concrete action from the audience. During the training process, participants were also equipped with a basic understanding of digital communication, particularly in utilizing social media platforms as a tool to expand the reach of messages. Creative content strategies, effective posting scheduling, and the use of visual storytelling were introduced so that NGO administrators could build a positive image of their institutions in the digital space. These skills are crucial considering that the dynamics of public communication today are influenced by the speed and reach of social media.The positive impact of this activity was felt not only individually, but also institutionally.The NGO